Optical and Electrical Characterization of Poly(3-Decylthiophene) Thin Films: Chloroform Sensor - Simõis, André V.S. [UNESP]; Ferreira, Nyara D. [UNESP]; Medina, Maria E.R.S. [UNESP]; Junior, Luiz A.R. [UNESP]; Borro, Marcelo S. [UNESP]; Olivati, Clarissa A. [UNESP] (FapUNIFESP (SciELO), 2024)
Conjugated polymers have attracted considerable attention to the organic electronics field, due to their properties and a variety of potential areas of application, such as solar cells, OLEDs, sensors, and transistors. In the sensor area, the study of chloroform gained prominence due to its toxicity and effects on the human body, such as damage to the liver and kidneys. This work aims to study thin films of P3DT in different concentrations, perform their optical, morphological, and electrical characterization, and verify their applicability as chloroform sensors. The thin films and devices are characterized using various techniques: optical characterization is performed through UV-vis spectroscopy, morphological characterization is performed through optical microscopy and electrical characterization is performed in direct current by studying the current vs. voltage curves. Electrical measurements of current vs. time are also performed in order to verify the electrical response of the active layer when exposed to a saturated chloroform atmosphere. Characterization shows expected results, similar to other P3ATs, while gas response initially shows a release in trapped charges, increasing the current, however, as the measure is repeated, the current started to decrease when exposed to the current, caused by a swelling in the polymer’s chain.
Keywords: chloroform; drop casting; gas sensor